(untitled) (Bioscience Journal, 2021)
Successive mowing are the major maintenance costs of lawns. Thus, both the expenditure with mowing and the visual and physiological aspect of the lawn have led to the search for alternatives to mechanical management. Thus, this work aimed to study the effects of different rates of imazapic herbicide applied alone or combined with imazapyr as a growth regulator of Bahiagrass (Paspalum notatum) and St. Augustine grass (Stenotaphrum secundatum). The experimental design was a randomized block with four replicates, and the treatments consisted of six rates of imazapic herbicide (35; 70; 105; 140; 175 and 210 g a.i. ha-1) for both species, three rates of imazapic + imazapyr in tank mix (15.57 + 5.25; 23.625 + 7.875; 32.5 + 10.5 g a.i. ha-1) for Bahiagrass and four rates of imazapic + imazapyr mixture (7.875 + 2.625; 15.57 + 5.25; 23.625 + 7.875; 32.5 + 10.5 g a.i. ha-1) for St. Augustine grass. The effect of the treatments was evaluated by observing visible injury symptoms, canopy height, height and number of inflorescences and total dry matter of clippings. Applications of imazapic alone or combined with imazapyr were effective in reducing plant height, number and height of inflorescences and total amount of dry matter of clippings produced by Bahiagrass plants. Imazapic provided satisfactory control of St. Augustine growth, but its utilization caused an increase in the number of inflorescences present in the lawns.